2017
DOI: 10.17756/jfcn.2017-039
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of Leaves of Trigonella foenum-graecum L. (Fenugreek): Leads from Preclinical Studies

Abstract: Diabetes mellitus, a metabolic disorder of the endocrine system is one of the World's oldest diseases known to man. Since time immemorial plants have been used as anti-diabetic agents in the various traditional systems of medicine. Trigonella foenum-graecum commonly known as fenugreek in English and methi in various Indian languages is one such plant and has been an integral part in the treatment of diabetes in the Indian traditional system of medicine the Ayurveda. The seeds and leaves have been documented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Moreover, because fenugreek contains a wide range of active factors, studies suggest that it may play a role in improving T2DM as an amino acid. 4-Hydroxyisoleusine [19] has also been shown to stimulate insulin secretion [12] , as well as alkaloids, trigonelline, which has anti-diabetic activity by improving the insulin-signaling pathway [15] , and flavonoids, which have antioxidant properties that protect the pancreas from the damages of free radicals [1] Therefore, this research was conducted to study the organic extract (ETAC e.x) with three different concentrations (12.5, 25 and 50 mg/ml) (groups PC1, PC2, and PC3) on alloxan-induced diabetic mice compared to normal, diabetic, and Glimepiride controls (groups NC, DC, and PC). Alloxan, a urea-derived chemical, is the most commonly used chemical agent for inducing DM in trial animals such as mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because fenugreek contains a wide range of active factors, studies suggest that it may play a role in improving T2DM as an amino acid. 4-Hydroxyisoleusine [19] has also been shown to stimulate insulin secretion [12] , as well as alkaloids, trigonelline, which has anti-diabetic activity by improving the insulin-signaling pathway [15] , and flavonoids, which have antioxidant properties that protect the pancreas from the damages of free radicals [1] Therefore, this research was conducted to study the organic extract (ETAC e.x) with three different concentrations (12.5, 25 and 50 mg/ml) (groups PC1, PC2, and PC3) on alloxan-induced diabetic mice compared to normal, diabetic, and Glimepiride controls (groups NC, DC, and PC). Alloxan, a urea-derived chemical, is the most commonly used chemical agent for inducing DM in trial animals such as mice.…”
Section: Discussionmentioning
confidence: 99%
“…In many animal [1,9,10] and human [5,11] studies, fenugreek has been revealed to have anti-diabetic properties. Many active elements are included in fenugreek seeds, such as the alkaloid (Trigonelline), amino acid (4-Hydroxyisoleucine), galactomannan, and flavonoids, which are suspected to be responsible for its hypoglycemic effects [12][13][14] . More exhaustive mechanistic studies have suggested that 4-hydroxyisoleucin improves insulin secretion, galactomannan reduces insulin resistance and glucose resorption from the gut, trigonelline stimulates β-cell regeneration [15], and inhibitory activity against α-amylase and α-glucosidase might well be due to the existence of polyphenols and flavonoids (vitexin, tricin, naringenin, quercetin, and tricin-7-O-beta-D-glucopyranoside) in fenugreek [16] .…”
Section: Introductionmentioning
confidence: 99%
“…It is been used as aphrodisiac agent for revitalization of humans from problems associated with digestive & respiratory (bronchial) systems, gout and arthritis. The fenugreek seeds are used to treat liver cancer, blood pressure and diabetes, simultaneously have found its place in myriad of medical formulations all across the world [90,91]. Subhapriya et al used the leaf extracts of fenugreek plants and a high temperature sintering method for the synthesis of TiO2 nanoparticles.…”
Section: Tio2 Npsmentioning
confidence: 99%
“…Najnowsze badania sugerują, iż nasiona kozieradki posiadają właściwości przeciwcukrzycowe, hipocholesterolemiczne, przeciwutleniające, przeciwnowotworowe, przeciwdrobnoustrojowe, stymulujące laktację oraz immunomodulujące. Do substancji czynnych znajdujących się w nasionach kozieradki zalicza się: śluzy, alkaloidy (trygonelina, karpaina, gencjanina), aminy biogenne (trimetyloamina, cholina), saponiny steroidowe (diosgenina, tigogenina, gitogenina), flawonoidy (witeksyna, luteolina, orientyna, kwercetyna) i fitosterole [20]. Mechanizm działania kozieradki pobudzający laktację nie jest jasny.…”
Section: Kozieradka Pospolita (Trigonella Foenum-graecum L)unclassified